PERAN WALI SONGO DALAM MENYEBARKAN AGAMA ISLAM DI INDONESIA - Purhasanah, Siti; Rohmatulloh, Rifqi; Al Ayyubi, Ibnu Imam (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
The spread of Islam to the archipelago started with merchants who wanted to trade in the archipelago. In pre-Wali Songo, precisely in the 12-13th century, the system of spreading Islam was by the da'wah method, with various multi-beliefs and cultures in society, so that the significance of belief in Islam amid society was marked by the emergence of new kingdoms, namely Islamic kingdoms with strength and followers with large numbers, then non-Islamic kingdoms at that time decreased in strength due to the proportion that became a minority. The method used in this study is a descriptive qualitative research method with a literature study approach that refers to several research data sources and data collection techniques in the form of wali songo studies. The focus of the research that will be raised is the role of the Wali Songo in spreading Islam in Indonesia. The data collection technique used in this study was the library research method, namely library research and the data analysis technique used in this study was a descriptive method. In spreading the teachings of Islam, Wali Songo has several strategies that can be accepted by the community by infiltrating local wisdom in Indonesia.